แนวทางการบริหารจัดการเพื่อลดผลกระทบระหว่างการก่อสร้าง แก่ผู้ใช้สอยอาคารข้างเคียง : กรณีศึกษา อาคารที่ก่อสร้างในโรงพยาบาลรัฐ - อลงกรณ์ ชาไชย (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
To determine management guidelines to reduce the impacts on patients and healthcare staff caused by construction sites in government-run hospitals. The study was firstly conducted on the impacts of the construction process on doctors, nurses and other medical staff as well as the patients in the buildings next to the construction sites. Secondly, the operation of the managerial team consisting of the project owners, the engineers and the construction administrations was considered. Finally, different case studies on issues concerning building construction were analyzed in order to arrive at guidelines to reduce impacts on people in the vicinity as stated. According to the research findings, the three main problems that affected building users were noise, vibration and particulate matter pollution, respectively. However, measures to prevent or alleviate the problems had not been property carried out due to seven related factors: the construction site, construction time, budget, relevant law, the building model, construction methods, and the nearby buildings. Proper management procedures can be used to reduce the impacts on people in the building. To illustrate, a long-term plan, sufficient staff, budget preparation, clear construction regulations, choosing a capable construction company and collecting statistical information on the impacts of construction must be included in the guidelines. In conclusion, cooperation of all building users and complete guideline implementation are necessary in order to reach the expected goals which would help upgrade the standards of the construction industry.